Effects of chemical composition on N, Ca, and Mg release during incubation of leaves from selected agroforestry and fallow plant species - Tian, G.; Kang, B.; Brussaard, Lijbert (1992)
Nitrogen, Ca and Mg release from leaves of ten selected plant residues with varying chemical compositions was studied under laboratory conditions. Three patterns of N-release were observed over a seven week incubation period: (a)Gliricidia sepium, Leucaena leucocephala, Mucuna pruriens andCentrosema pubescens leaves showed rapid N release, (b)Acioa barteri andDialium guineense leaves immobilized N, and (c)Alchornea cordifolia, Anthonata macrophylla, Cassia siamea andPterocarpus santalinoides leaves initially showed N immobilization which gradually changes to net mineralization after about four weeks of incubation. Nitrogen mineralization rate constant (k) ranged from −0.0018 (A. barteri) to 0.0064 day−1 (G. sepium). Statistical analysis of data showed that N mineralization rate constants are significantly correlated with initial N, polyphenol and lignin contents of leaves. Nitrogen release increased with increasing N content and decreased with increasing contents of polyphenols and lignin. Addition of leaves from all species significantly increased soil exchangeable Ca and Mg levels.L. leucocephala, G. sepium, C. pubescens andM. pruriens showed relatively high Ca and Mg release rates. Calcium release rate was related to N release rate rather than to initial Ca content.